Prevalence of HIV among Tuberculosis Out Patient Attendees - Thiruvalluvan, E; Shenbagavalli, R; Mohana, M (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Background : An estimated 2.47 million (2.0-3.1 million) people were living with HIV/AIDS in India by the end of 2006. Among those HIV infected individuals, TB was the commonest opportunistic infection and leading cause of mortality. HIV infection makes a person susceptible to both pulmonary and extra pulmonary forms of TB. Various studies have documented the occurrence of TB from 46 to 65 percent. However, provision of HIV screening services for Tuberculosis out patient attendees is limited at present. Aims : To study feasibility of counseling for HIV screening and document the prevalence of HIV among TB out patient attendees. Methods : This prospective explorative study included persons who sought TB screening at TB unit, Madurai from Jan 2003- Feb 2004. An interview schedule was developed to obtain information on socio-demographic profi le, risk behavior profi le and test results. Information collected includes socio-demographic profile, risk behavior profi le and reaction to test results. Univariata and bivariate analyses were performed using Epi-info 6.04 (CDC, Atlanta, GA, July 1996). Chi-square test, student "t" test and one way ANOVA tests were performed to establish statistical signifi cance between dependent and independent variables Results : This study has found 57.66% chest symptomatic attending TB out patient ward were HIV positive. An analysis of risk profile versus positive results showed that 47(n=75) and 48(n=90) who admitted and denied high-risk behavior respectively, found to be positive to HIV screening test. Conclusion : The researchers suggest that HIV counseling and testing services can be offered to all chest symptomatic attending TB out patient ward. This structural change will make HIV screening more effective and benefi cial to patient community by ensuring early detection HIV infection. DOI: 10.3126/saarctb.v6i1.3060 SAARC J. Tuber. Lung Dis. HIV/AIDS 2009 VI (1) 16-24